Empowered by Spirit: Women’s Existential Struggles in Latife Tekin’s Novels - Danış, Zeynep Kevser Şerefoğlu; Şişman, Gönül Yonar (Palgrave Studies, 2025)
Introduction: Spirituality and the Feminine Journey in Postmodern Literature In the trajectory of literature from modernism to postmodernism, it has become increasingly evident that literary texts often turn to spiritual enchantment as an alternative to the “obstinate spells of modernity.” Day by day, the enchantment aspect of literature has grown more prominent. The realism and naturalism rooted in nineteenth-century positivism, which once dominated art, have contributed to this development. An artistic environment in which fiction was valued primarily for its close rela¬tion to reality—or even its direct correspondence to reality—inevitably sought to escape from that suffocating climate. The appearance of spiritual inclinations in postmodern literature after the 1970s can be seen as a reac¬tion against the former pressure of strict realism.